Search for a light Higgs resonance in radiative decays of the [upsilon](1S) with a charm tag - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
A search is presented for the decay Υ(1S)→γA0, A0→c¯c, where A0 is a candidate for the CP-odd Higgs boson of the next-to-minimal supersymmetric standard model. The search is based on data collected with the BABAR detector at the Υ(2S) resonance. A sample of Υ(1S) mesons is selected via the decay Υ(2S)→π+π−Υ(1S). The A0→c¯c decay is identified through the reconstruction of hadronic D0, D+, and D∗(2010)+ meson decays. No significant signal is observed. The measured 90% confidence-level upper limits on the product branching fraction B(Υ(1S)→γA0)×B(A0→c¯c) range from 7.4×10−5 to 2.4×10−3 for A0 masses from 4.00 to 8.95 GeV/c2 and 9.10 to 9.25 GeV/c2, where the region between 8.95 and 9.10 GeV/c2 is excluded because of background from Υ(2S)→γχbJ(1P), χbJ(1P)→γΥ(1S) decays.